Evaluation of the Performance of Fiber-Reinforced Mortars Based on Dredged Sludge - Mohamed, Salhi; Amar, Benyahia; Li, Alex; Boubekeur, Toufik; Ashour, Ashraf; Said, Choucha (International Journal of Engineering Research in Africa, 2024)
River-carried solids, especially during floods, lead to dam sedimentation. Dredging extends dam life, but excess unusable sediment storage threatens the environment. The aim of this work is to investigate the influence of the recovery of calcined mud from Chorfa dam on the physico-mechanical and chemical characteristics of mortars fiber bundles. The sludge is used as a partial substitute for cement by volume at rates of 10%, 15%, 20% and 25%. All test specimens had water / binder (W/B) ratio and steel fibers ratio. Testing programme included measuring the fluidity, ultrasonic pulse velocity test, dynamic modulus of elasticity, flexural and compressive strengths. Compared to the control mortar, the fluidity represented by the diameter of M0, M15 and M25 mixtures decreased by approximately 11%, 14% and 22%, respectively. The compressive strength of M15 increased by 17.4% at 28 days, compared with the control specimen. At 7 days, the ultrasonic speed of the M25 mixture decreases by 1.7% compared to that of M15. The dynamic modulus of elasticity of M20 and M25 increases by 13% and 12% as the age ranges from 2 to 28 days. At 28 days, the flexural strength of the M20 blends increased by approximately 64%.